Efectividad del tratamiento de mastocitoma cutáneo múltiple de alto grado usando un inhibidor de tirosina quinasa y vinblastina: reporte de caso - Mujica, Paola C. (2021)
Cutaneous mast cell tumour is the most common skin neoplasm in dogs. The case of a 10-year-old female Shar Pei canine patient is presented, who presented in consultation with multiple erythematous masses on the medial aspect of the right hind limb. By cytological and histopathological examination, high-grade mast cell tumour was diagnosed. The patient was treated with omeprazole and with a chemotherapy protocol based on a combination of vinblastine, prednisone, and a tyrosine kinase inhibitor. During the monthly follow-up of the evolution of the patient, partial remission of the masses was observed, which remained stable for seven months, at which time it was decided to suspend the use of vinblastine. After a month of this change, there was no recurrence of the previously treated masses; however, the appearance of new erythematous and ulcerated neoplasms in another region of the affected hind limb was evidenced. This observation supports the hypothesis that the genetic nature of neoplasms of the same type, in the same patient, could be different and, therefore, determine the response to treatment and prognosis.